Circ_0005918 Sponges miR-622 to Aggravate Intervertebral Disc Degeneration - Cui, Yan; Zhao, Xintong; Wu, Yangang (Frontiers in Cell and Developmental Biology, 2022)
Intervertebral disc degeneration (IDD) is the most common cause of low back pain and the exact molecular mechanism of IDD is still unknown. Recently, studies have showed that circular RNAs (circRNAs) regulate diverse biological procedures such as cell metastasis, growth, metabolism, migration, apoptosis and invasion. We demonstrated that IL-1β and TNF-α induced circ_0005918 expression in the NP cell and circ_0005918 was overexpressed in the IDD group compared with the control group. Moreover, the upregulated expression of circ_0005918 was associated with disc degeneration degree. Elevated expression of circ_0005918 promoted cell growth and ECM degradation and induced secretion of inflammatory cytokines including IL-1β, IL-6 and TNF-α. Moreover, we found that crc_0005918 sponged miR-622 expression in the NP cell. In addition, exposure to IL-1β and TNF-α suppressed expression of miR-622, which was downregulated in the IDD group compared with the control group. Furthermore, the downregulated expression of miR-622 was associated with disc degeneration degree. The level of miR-622 was negatively associated with circ_0005918 expression in IDD group. Circ_0005918 regulated cell growth, ECM degradation and inflammatory cytokines secretion through regulating miR-622 expression. These data suggested that circ_0005918 plays important roles in the development of IDD via sponging miR-622.